Genetic diversity of macaúba fruits from 35 municipalities of the state of Goiás, Brazil - Reis, Edésio Fialho dos; Pinto, Jefferson Fernando Naves; Assunção, Hildeu Ferreira da; Silva, Danielle Fabíola Pereira da (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the genetic diversity of macaúba (Acrocomia aculeata) accessions from 35 municipalities of the state of Goiás, Brazil, in order to obtain information about the genetic variability and to provide subsidies for the commercial deployment of the culture in the Midwestern region of Brazil. The bunches were harvested with ripe fruits. The following were evaluated: fruit and almond lengths and diameters; the weights of fruits and almonds; the average number of almonds, as well as the oil contents in the almond and in the dehydrated fruit. The parameters that indicated significant contributions to the variability were fruit weight, fruit width, fruit length, and oil content in the almond.